MANAJEMEN KONFLIK DALAM NEPOTISME PENGANGKATAAN JABATAN - Lidya Dwi Jayanti; Tabah Maryanah; Robi Cahyadi Kurniawan (Halu Oleo University, 2024)
Traditional society has a main obligation, namely helping its family members. This attitude is also often applied by today's society which has the potential to be carried out by certain officials to pass their colleagues and family into work. As a result, others who are more worthy have no chance of taking the job. The purpose of this research is to find out conflict management in office appointment nepotism and to find out solutions in dealing with nepotism cases in the recruitment and selection process. This study uses a literature study method. The results of the study show that the Provincial Government has taken several actions to handle regulatory conflicts related to nepotism in Indonesia as stated in Law Number 28 of 1999 concerning the Administration of a State that is Free and Clean from Corruption, Collusion, and Nepotism. The law first explains the importance of cracking down on nepotism.